A Jungian Reading Of President Snow’s Identity In The Hunger Games Series - Sadiya Damar Maritza (Samudra Ilmu Indonesia, 2026)
This study examines the psychological construction of Coriolanus Snow’s identity in The Hunger Games film series through the lens of Carl Gustav Jung’s analytical psychology. Utilizing a qualitative approach within a psychoanalytic literary criticism framework, this research deconstructs the volatile, dynamic interaction between Snow’s conscious Persona and his repressed Shadow. Through thematic textual and visual analysis of the films, the study evaluates how his public facade of prestige, order, and authority masks a darker subconscious realm driven by survival trauma, acute paranoia, and socioeconomic anxiety. The findings reveal that Snow’s identity is not static but is continuously constructed by the conflict between these two realms. His failure to consciously integrate his vulnerable Shadow causes it to aggressively hijack his ego. Consequently, the tension between maintaining a flawless Persona and suppressing the Shadow ultimately transforms his identity, mutating youthful idealism into systemic authoritarian tyranny, moral disintegration, and profound psychological fragmentation.